Design and development of 10 WP Solar panel tracking system based on RTC and Arduino - Esron S. Sibarani; Dina Maizana; Moranain Mungkin; Muzamir Isa; Govinda Prashad Pandey (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2022)
Currently, the use of solar panels in Indonesia is still in a stationary position (static) so that the absorption of sunlight is less than optimal due to frequent weather, cloudy weather, and during the afternoon until the afternoon the suns light has turn back/or is not parallel to the solar panels. To obtain optimal electrical energy, the solar panel systems must be equipped with a control-systems and equipped with an RTC (Real Time Clock) sensor module which functions to provide real time data/or components to adjust the direction of the surface of the solar panel so that it always faces the sun at a given angle (tracking based on the movement of the earth) so that the energy from the suns ray can completely fall to the surface of the solar panel. And from the data obtained on December 13, 2021, the output produced by a 10 Wp solar panel tracking system for 9 (nine) hours with a 5 Watt lamp load produces a total power of 3.392 Wh while a non-tracking 10 Wp solar panel produces a total power of 19.658 Wh and the difference between the two 10 Wp solar panels is 15.732 Wh.